Slovakia: Open Land Market and No Restrictions - Szilágyi, János Ede; Szinek Csütörtöki, Hajnalka (Acquisition of Agricultural Lands, 2022)
Slovakia’s accession to the European Union opened a whole new chapter in the country’s history and brought dynamic changes to its land transfer regulation. In the Slovak Republic, the moratorium forbidding the purchase of agricultural land by foreigners expired in 2014. Following this period, the European Commission launched a comprehensive examination regarding land acquisition regulations in the newly acceded member states. The investigation revealed that specific provisions of the Slovak land regulation restricted the EU’s fundamental economic freedoms. The Slovak legislator responded to this situation by amending a particular paragraph of the Foreign Exchange Act, which has resulted in opening the agricultural land market not only to EU nationals but also to third-country nationals. In addition, several new rules concerning this subject were adopted, namely the Act on the acquisition of ownership of agricultural land. It should be noted that even before the mentioned revelation, this Act had been the subject of numerous public debates. Consequently, the Constitutional Court of the Slovak Republic annulled a significant part of the Act on land acquisition in its decision on November 14, 2018, which has contributed to the agricultural land market becoming fully open in Slovakia.This chapter introduces the current legislation on land protection and characterizes the rules on agricultural land regulation and land transfer law in Slovakia, exploring the constitutional level with particular regard to the decision delivered by the Constitutional Court of the Slovak Republic in detail. Moreover, the proceeding initiated by the European Commission is also a subject of this study. Finally, the national legal instruments of Slovakia are also analyzed in light of the Commission’s Interpretative Communication. Keywords: land law, cross-border land acquisitions, agricultural land, Slovakia